Case report: skeletal muscle metastasis from follicular thyroid carcinoma presenting as synovial sarcoma - Stergioula, Anastasia; Pantelis, Evaggelos; Kormas, Theodoros; Agrogiannis, Georgios (Frontiers in Oncology, 2023)
Differentiated thyroid carcinomas tend to remain localized and usually are of slow progression with excellent long-term survival. The major sites of distant metastases are cervical lymph nodes, lungs and bones and the minor sites include the brain, liver, pericardium, skin, kidney, pleura and muscle. Skeletal muscle metastases from differentiated thyroid carcinoma, is exceedingly rare. In this report, a 42-year-old woman with follicular thyroid cancer that had had a total thyroidectomy and radioiodine ablation nine years ago was presented with a painful right thigh mass and negative PET/CT scan. The patient had also lung metastases during the follow-up period which were treated with surgery, chemotherapy and radiation therapy. An MRI scan of the right thigh showed a deep-seated lobulated mass, with cystic regions, bleeding elements and strong heterogeneous post contrast administration enhancement. Due to the similarities in clinical manifestations and imaging features between skeletal muscle metastases and soft tissue tumors, the case was initially misdiagnosed in favor of synovial sarcoma. Histopathological, immunohistochemistry and molecular analysis of the soft tissue mass confirmed to be a thyroid metastasis, and a final diagnosis of skeletal muscle metastases was provided. While the probability of a skeletal muscle metastasis from thyroid cancer approaches zero, this study aims to raise the awareness to the medical community that these events do in fact occur in the clinical setting and should be considered in the differential diagnosis of patients with thyroid carcinomas.